2023
DOI: 10.1039/d3me00047h
|View full text |Cite
|
Sign up to set email alerts
|

Influence of anions on the synthesis of Cu(i)-based coordination polymers along with a series of derived materials for selective photocatalytic properties

Abstract: Coordination polymers (CPs) are a scientifically compelling and evolving class of highly crystalline materials. Owing to their controllable structures and morphologies, CPs can be used as a type of uniformly...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 67 publications
(74 reference statements)
0
0
0
Order By: Relevance
“…The mechanism of the photocatalytic dye degradation with the Cu­(I) framework is well established. ,, In general, upon exposure to light, the Cu­(I) CPs absorb photons and generate electrons, possessing energies equal to or exceeding the band gap. These electrons undergo a transition from the highest occupied molecular orbitals to the lowest unoccupied molecular orbitals of the polymer, ultimately reaching the surface of (CuI) n clusters, thereby producing electron–hole pairs .…”
Section: Mechanism Of the Catalytic Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of the photocatalytic dye degradation with the Cu­(I) framework is well established. ,, In general, upon exposure to light, the Cu­(I) CPs absorb photons and generate electrons, possessing energies equal to or exceeding the band gap. These electrons undergo a transition from the highest occupied molecular orbitals to the lowest unoccupied molecular orbitals of the polymer, ultimately reaching the surface of (CuI) n clusters, thereby producing electron–hole pairs .…”
Section: Mechanism Of the Catalytic Reactionmentioning
confidence: 99%
“…The abundant presence of copper iodide metal clusters contributes to the semiconducting nature of the synthesized CPs. Recent studies have shown that while Cu­(I) CPs are effective in degrading dyes, they have the drawback of prolonged dye degradation time and low recyclability. , The applicability of CP1 and CP2 was also explored as photocatalysts for the degradation of methylene blue (MB) and rhodamine B (RHB) under sunlight. Our compounds show excellent photocatalytic efficiency with less time and high recyclability.…”
Section: Introductionmentioning
confidence: 99%